Meningkatkan Kinerja Kepala Sekolah dalam Melaksanakan Supervisi Kelas melalui Supervisi Manajerial Pengawas pada Sekolah Binaan di Kecamatan Masbagik Kabupaten Lombok Timur - Nurdin, Nurdin (MASALIQ, 2021)
The purpose of this action research is to determine the extent of the influence of managerial supervision in improving the performance of principals at the target schools in the Masbagik district for the 2021-2022 school year. In this action research was carried out in 2 cycles, from the results of the actions taken it was proven to be able to improve the performance of the principal by achieving the ideal standard. From 63% in Cycle I, it could increase to 89% in Cycle II. The results of this action research indicate that the supervision of supervisors through managerial supervision is effective in improving the performance of school principals in the fostered schools of East Lombok Regency.